2003
DOI: 10.1521/pedi.17.2.129.23989
|View full text |Cite
|
Sign up to set email alerts
|

The Core Elements of Neurosis: Mixed Anxiety-Depression (Cothymia) and Personality Disorder

Abstract: Although there has been great diagnostic activity within the conditions formally included under the general rubric of neurosis in the last 20 years, there is little evidence that the many new diagnoses (i.e., generalized anxiety disorder, panic disorder, social anxiety disorder, and dysthymic disorder) have helped clinicians and improved the health of those diagnosed. This is largely because of the extensive comorbidity between these disorders negates much of their attempted separation and it is argued that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…There is a strong association of PD comorbidity with earlier age of onset (Brieger et al 2002, Ozkan & Altindag 2005; greater clinical severity (Ozkan & Altindag 2005); poorer treatment outcome (Farabaugh et al 2005, Ogrodniczuk et al 2001; longer time to remission (Grilo et al 2005, Massion et al 2002; lower long-term social, cognitive, and occupational functioning (Bank & Silk 2001, Denys et al 2004, Smith & Benjamin 2002, Tyrer et al 2003; greater medical utilization (Smith & Benjamin 2002); suicide attempts and completion (Garno et al 2005, Hawton et al 2003; and greater risk of psychopathology in offspring (Abela et al 2005). However, worse outcome-including increased time to remission-is not inevitable (Grilo et al 2000), varies by PD (Grilo et al 2005), and to some extent may reflect methodological flaws rather than true effects (Mulder 2002).…”
Section: Complications Of Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong association of PD comorbidity with earlier age of onset (Brieger et al 2002, Ozkan & Altindag 2005; greater clinical severity (Ozkan & Altindag 2005); poorer treatment outcome (Farabaugh et al 2005, Ogrodniczuk et al 2001; longer time to remission (Grilo et al 2005, Massion et al 2002; lower long-term social, cognitive, and occupational functioning (Bank & Silk 2001, Denys et al 2004, Smith & Benjamin 2002, Tyrer et al 2003; greater medical utilization (Smith & Benjamin 2002); suicide attempts and completion (Garno et al 2005, Hawton et al 2003; and greater risk of psychopathology in offspring (Abela et al 2005). However, worse outcome-including increased time to remission-is not inevitable (Grilo et al 2000), varies by PD (Grilo et al 2005), and to some extent may reflect methodological flaws rather than true effects (Mulder 2002).…”
Section: Complications Of Comorbiditymentioning
confidence: 99%
“…Tyrer et al (2003) suggest that splitting the traditional category of neurosis into specific disorders [e.g., generalized anxiety disorder (GAD), social phobia, dysthymia] was neither helpful nor warranted because of their www.annualreviews.org • Personality Disorder Assessment and Diagnosisextensive comorbidity. They argue provocatively that their results demonstrate "a failed classification system," that much comorbidity is really "consanguinity," and that current diagnostic concepts have little impact and "are relatively useless" (p. 136).…”
Section: Comorbidity With Depression and Anxiety Disordersmentioning
confidence: 99%
“…In this study, instead of evaluating them separately, we have compared SD and PD and have found significantly higher rates of borderline, obsessive-compulsive, avoidant and passive-aggressive personality disorders in PD cases. All of these personality disorders except the borderline personality disorder others belong to the cluster C, which is also known as the anxious cluster, and have clinical pictures sharing high comorbidity with neuroticism (20,21). Among the cognitive-behavioral approaches, the most commonly adopted one about the development of PD is the 'anxiety sensitivity' theory, which has been shown to correlate positively with the personality disorders in cluster C (21).…”
Section: Discussionmentioning
confidence: 99%
“…I personally would wish them to do the same for the most common disorder in psychiatry, mixed anxiety and depression, which when linked to personality disorder is described as the general neurotic syndrome (Andrews et al, 1990;Tyrer, 1985;Tyrer, Seivewright, & Johnson, 2003), but which does not attract the same interest, as the adjective "neurotic" is now completely rejected in psychiatry.…”
Section: Table 1 a System For The Grading Of Diagnostic Systems And mentioning
confidence: 99%